2021
DOI: 10.1182/bloodadvances.2020003353
|View full text |Cite
|
Sign up to set email alerts
|

HIGH-2-LOW risk model to predict venous thromboembolism in allogeneic transplant patients after platelet engraftment

Abstract: Venous thromboembolism (VTE) after allogeneic hematopoietic cell transplantation (HCT) is a significant treatment-associated complication, although optimal timing of thromboprophylaxis remains uncertain when weighing concurrent risks of bleeding. We aimed to derive and internally validate a risk assessment model (RAM) using patients who underwent first allogeneic HCT from 2006 through 2015 (n = 1703). Index date was defined as the 30th day after transplant, at which point we estimated >75% of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Although those cases were not included in the present analyses, we have previously shown that HIGH-2-LOW works similarly well when applied to this patient population. 8 Second, an important proportion of VTE events corresponded to CVC-DVT, with a higher prevalence in the MDACC than the FHCRC cohort. The present study did not incorporate into the analyses any specific factors inherent to risk for thrombosis associated to CVC-DVT, such as catheter features (diameter, number of lumens), location of the tip and side of insertion, insertion techniques, and duration before exchange.…”
Section: Table S5 Highlightsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although those cases were not included in the present analyses, we have previously shown that HIGH-2-LOW works similarly well when applied to this patient population. 8 Second, an important proportion of VTE events corresponded to CVC-DVT, with a higher prevalence in the MDACC than the FHCRC cohort. The present study did not incorporate into the analyses any specific factors inherent to risk for thrombosis associated to CVC-DVT, such as catheter features (diameter, number of lumens), location of the tip and side of insertion, insertion techniques, and duration before exchange.…”
Section: Table S5 Highlightsmentioning
confidence: 96%
“…The discrimination of this score had a c statistic of 0.69 (0.62-0.76) in the original study. 8 The objective of the present study was to perform a temporal and external validation of the HIGH-2-LOW VTE RAM after platelet engraftment in two independent datasets. Patients who died, received inpatient or outpatient anticoagulation (based on pharmacy data), or did not achieve platelet engraftment by day 30 were excluded.…”
Section: Introductionmentioning
confidence: 99%
“…91 In this study, neither patient sex nor hormone replacement therapy among females were associated with thrombosis risk. Likewise, Martens et al 76 studied risk factors for VTE in days 30 through 100 post-HCT and found no difference in risk based on sex.…”
Section: Hematopoietic Cell Transplantmentioning
confidence: 99%
“…We captured additional time-varying covariates within the first 30 days post-HCT, including the decision to resume anticoagulation (or not) after platelet engraftment (defined as platelets >50 Â 10 9 /L without transfusion support), and components of the recently derived HIGH-2-LOW risk assessment score. 13 This risk assessment model, which incorporates seven clinical predictors, helps stratify allogeneic HCT patients not on therapeutic anticoagulants by day 30 into risk categories for VTE. These predictors, with their assigned integer scores, include: history of CR-DVT (+1), inpatient admission at day 30 (+1), GVHD grade 3-4 at day 30 (+1), history of PE or LE-DVT (+2), lymphoid diagnosis (+1), obesity with body mass index ≥35 kg/m 2 (+1), and white blood cells ≥11 Â 10 9 /L at day 30 (+1).…”
Section: Risk Factors For Vte Recurrence Beyond 30 Daysmentioning
confidence: 99%
“…In our recent study of VTE in the allogeneic HCT setting, we identified patients with history of VTE at higher risk for the development of VTE after HCT. 13 Our study was limited, however, by the exclusion of patients on anticoagulants at the time of HCT. Thus, how to manage patients on anticoagulation for history of VTE during the post-HCT period remains unanswered.…”
Section: Introductionmentioning
confidence: 99%